2000
DOI: 10.1176/jnp.12.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dementia and Alzheimer's Disease: Is There a Difference?

Abstract: This study examined differences between vascular dementia (VaD) by the NINDS/AIRENS criteria and Alzheimer's disease (AD) on clinical grounds. A consecutive series of 517 patients with probable and possible VaD or AD were evaluated for cognitive, functional, and behavioral symptoms and separated into three subgroups by duration of dementia. These AD and VaD subgroups were then compared on a series of standardized clinical measures. The only consistent trends were for VaD patients to be more depressed, more fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…Any observed primary local damage could also be attributed to vascular injury, as white matter is particularly sensitive to vascular disruption (Mandell et al 2008;Wang et al 2016;Li et al 2016) and cerebrovascular disease is highly comorbid with AD (Toledo et al 2013;Smith 2017). However, there is a considerable overlap in the findings that are conventionally attributed to purely AD and purely vascular neuropathologies (Groves et al 2000;de la Torre 2004;Girouard and Iadecola 2005;Kalaria and Ballard 2006;Rodrigue 2013), with many proposing that vascular disruption may be central to AD as well (Moody et al 1997;de la Torre 2002de la Torre , 2004Kalaria et al 2012;Cai et al 2015;Brickman et al 2015). The intersection of AD and VCI may be most apparent in leukoaraiosis (Clarke et al 2000;Pettersen et al 2008;Kalaria et al 2012;Cai et al 2015;Brickman et al 2015;Lee et al 2016).…”
Section: White Matter Changes In Alzheimer Diseasementioning
confidence: 99%
“…Any observed primary local damage could also be attributed to vascular injury, as white matter is particularly sensitive to vascular disruption (Mandell et al 2008;Wang et al 2016;Li et al 2016) and cerebrovascular disease is highly comorbid with AD (Toledo et al 2013;Smith 2017). However, there is a considerable overlap in the findings that are conventionally attributed to purely AD and purely vascular neuropathologies (Groves et al 2000;de la Torre 2004;Girouard and Iadecola 2005;Kalaria and Ballard 2006;Rodrigue 2013), with many proposing that vascular disruption may be central to AD as well (Moody et al 1997;de la Torre 2002de la Torre , 2004Kalaria et al 2012;Cai et al 2015;Brickman et al 2015). The intersection of AD and VCI may be most apparent in leukoaraiosis (Clarke et al 2000;Pettersen et al 2008;Kalaria et al 2012;Cai et al 2015;Brickman et al 2015;Lee et al 2016).…”
Section: White Matter Changes In Alzheimer Diseasementioning
confidence: 99%
“…Groves et al [30] observed that patients with VaD were more likely to experience long-standing depression with functional impairment on a long-term observational period, although AD patients were also observed to experience some degree of sleep disorders and depression according to the neurodegenerative trajectory.…”
Section: Behavioral Disturbances and Dementia Sub Types: Vascular mentioning
confidence: 99%
“…Whereas memory and language deficits prevail in AD, executive function is more affected in VaD, possibly due to the interruption of frontal networks [24]. Changes in mood and personality occur earlier and are more severe in VaD than in AD [25,26]. …”
Section: Vascular Dementia and Transcranial Magnetic Stimulation: An mentioning
confidence: 99%